The Impact of Auditor Characteristics on Key Audit Matters Disclosure in Indonesian Listed Companies - Kusumawati, Selfiah; Suhardianto, Novrys (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
Tp>This study examines the impact of external auditor characteristics on the disclosure of Key Audit Matters (KAM) in the Indonesian context. The characteristics considered include audit fees, educational background, gender, the size of the certified public accounting (CPA) firm, and auditor experience. Employing a quantitative approach, the study analyzed 1,383 IDX-listed companies from 2022 to 2023 using multiple linear regression with fixed effects to control for industry and year variations. The results indicate that CPA firm size has a significant negative effect on KAM disclosure, suggesting that companies audited by Big 4 firms tend to disclose fewer KAMs. In contrast, audit fees, education, gender, and auditor experience show no significant effects. These findings suggest that the complexity and scale of the audited company, together with the audit policies of the CPA firm, play a more decisive role in determining the extent of KAM disclosure than individual auditor characteristics.